ANALYSIS OF THE CURRENT STATE AND PROSPECTS OF THE DEVELOPMENT OF THE FINANCIAL SECTOR OF THE ECONOMY OF UKRAINE - Bondarenko , Mariya; Boyarko , Iryna (Socio-economic relations in the digital society, 2021)
In the current realities of the growth of financial globalization and ensuring the functioning of the financial market as an integral part of the market economic system the financial sector has become a dominant factor in development, political and social balance in the economy. Since the development and formation of the financial market of Ukraine is a necessary prerequisite for the development of other sectors of the economy, it is advisable to study the current condition of the financial market of Ukraine. Thus, the article identified the main structural elements of the financial sector of Ukraine by the degree of their development and their presence on the market. The dynamics of the number, assets and capital of companies in the financial sector of Ukraine, namely financial companies, insurance companies, banks and credit institutions over the past five years. The analysis of the financial market of Ukraine was conducted in three key segments: the banking sector, the insurance sector, and the stock market. The dynamics of the main indicators of development of the banking sector, insurance market of Ukraine, the dynamics of the Stock Market Index, the volume of exchange contracts with securities and their structure by traders, the dynamics of trading volume in the securities market and the volume of securities issues registered by the National Commission on Securities and Stock Market of Securities Issues, the structure of securities securities market with the distribution of financial instruments and the dynamics of capitalization of the stock market. As the modern financial market in Ukraine is still in the process of transformation in the domestic scientific environment, the prevailing opinion is that the financial market in Ukraine is underdeveloped, so the paper describes the main problems and directions of financial sector development, which will be a prerequisite for competitive integration of domestic financial companies into the world financial system.